No Effect of Thyroid Dysfunction and Autoimmunity on Health-Related Quality of Life and Mental Health in Children and Adolescents: Results From a Nationwide Cross-Sectional Study - Hirtz, Raphael; Keesen, Anne; Hölling, Heike; Hauffa, Berthold P.; Hinney, Anke; Grasemann, Corinna (Frontiers in Endocrinology, 2020)
Background: In adults, a significant impact of thyroid dysfunction and autoimmunity on health-related quality of life (HRQoL) and mental health is described. However, studies in children and adolescents are sparse, underpowered, and findings are ambiguous. Methods: Data from 759 German children and adolescents affected by thyroid disease (subclinical hypothyroidism: 331; subclinical hyperthyroidism: 276; overt hypothyroidism: 20; overt hyperthyroidism: 28; Hashimoto’s thyroiditis (HT): 68; thyroid-peroxidase antibody (TPO)-AB positivity without apparent thyroid dysfunction: 61) and 7293 healthy controls from a nationwide cross-sectional study (‘The German Health Interview and Examination Survey for Children and Adolescents’) were available. Self-assessed HRQoL (KINDL-R) and mental health (SDQ) were compared for each subgroup with healthy controls by analysis of covariance considering questionnaire-specific confounding factors. Thyroid parameters (TSH, fT4, fT3, TPO-AB levels, thyroid volume as well as urinary iodine excretion) were correlated with KINDL-R and SDQ scores employing multiple regression, likewise accounting for confounding factors. Results: The subsample of participants affected by overt hypothyroidism evidenced impaired mental health in comparison to healthy controls, but SDQ scores were within the normal range of normative data. Moreover, in no other subgroup, HRQoL or mental health were affected by thyroid disorders. Also, there was neither a significant relationship between any single biochemical parameter of thyroid function and HRQoL or mental health, nor did the combined thyroid parameters account for a significant proportion of variance in either outcome measure. Importantly, the present study was sufficiently powered to identify even small effects in children and adolescents affected by HT, subclinical hypothyroidism, and hyperthyroidism. Conclusions: In contrast to findings in adults, and especially in HT, there was no significant impairment of HRQoL or mental health in children and adolescents from the general pediatric population affected by thyroid disease. Moreover, mechanisms proposed to explain impaired mental health in thyroid dysfunction in adults do not pertain to children and adolescents in the present study.